Evidence, and replication thereof, that molecular-genetic and environmental risks for psychosis impact through an affective pathway. Issue 10 (19th July 2022) - van Os, Jim; Pries, Lotta-Katrin; ten Have, Margreet; de Graaf, Ron; van Dorsselaer, Saskia; Delespaul, Philippe; Bak, Maarten; Kenis, Gunter; Lin, Bochao D.; Luykx, Jurjen J.; Richards, Alexander L.; Akdede, Berna; et al.
Abstract: Background: There is evidence that environmental and genetic risk factors for schizophrenia spectrum disorders are transdiagnostic and mediated in part through a generic pathway of affective dysregulation. Methods: We analysed to what degree the impact of schizophrenia polygenic risk (PRS-SZ) and childhood adversity (CA) on psychosis outcomes was contingent on co-presence of affective dysregulation, defined as significant depressive symptoms, in (i) NEMESIS-2 ( n = 6646), a representative general population sample, interviewed four times over nine years and (ii) EUGEI ( n = 4068) a sample of patients with schizophrenia spectrum disorder, the siblings of these patients and controls. Results: The impact of PRS-SZ on psychosis showed significant dependence on co-presence of affective dysregulation in NEMESIS-2 [relative excess risk due to interaction (RERI): 1.01, p = 0.037] and in EUGEI (RERI = 3.39, p = 0.048). This was particularly evident for delusional ideation (NEMESIS-2: RERI = 1.74, p = 0.003; EUGEI: RERI = 4.16, p = 0.019) and not for hallucinatory experiences (NEMESIS-2: RERI = 0.65, p = 0.284; EUGEI: −0.37, p = 0.547). A similar and stronger pattern of results was evident for CA (RERI delusions and hallucinations: NEMESIS-2: 3.02, p < 0.001; EUGEI: 6.44, p < 0.001; RERI delusional ideation: NEMESIS-2: 3.79, p < 0.001; EUGEI: 5.43, p = 0.001; RERI hallucinatory experiences: NEMESIS-2: 2.46, p < 0.001; EUGEI: 0.54, p = 0.465). Conclusions: The results, and internal replication, suggest that the effects of known genetic and non-genetic risk factors for psychosis are mediated in part through an affective pathway, from which early states of delusional meaning may arise.